Pusat Jajanan Dan Cenderamata Khas Riau Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Akbar Sukirman Putra; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Riau has a vision as Malay culture center in southest asia 2025 will not materialize without community for conserve and develop Riau Malay culture. One of conserve Riau Malay culture is developing of heritage such as culinary and handicraft. This become a reason to develop foodcourt and handicraft about Riau Malay culture. This place will sell all culinary and handicraft about Riau Malay culture. this place also for a picnic and gathering with friend and family while enjoying playpark. In the design, use tropical architecture like a responsive to solar radiation and rainful, cros ventilation, vegetation and roof forms. characteristic of this place use concept recreation. its like a view, color, nature, movement and activity people. it has five volumes, that is a handicraft fasilities, culinary facilities and main fasilities. Beside that a outdoor consists of garden and pool.Keyword: Food and Souvenirs Center, Tropical Architecture, Recreation